2004
DOI: 10.1177/0095399703258698
|View full text |Cite
|
Sign up to set email alerts
|

What Really Happens during the Lachman Test?

Abstract: Rupture of the ACL leads to increased anterior tibial translation coupled with tibial internal rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Historically, the Lachman test has been the most accurate and reliable for diagnosing an ACL rupture, 22 and the pivot-shift test is notably thought of as the least sensitive of the three. 8 , 9 , 14 , 17 , 23 Previous studies 7 , 19 have demonstrated the lever sign test to be more sensitive in correctly diagnosing both acute and chronic ACL tears, as well as complete and partial ACL tears, as compared with the anterior drawer, Lachman, and pivot-shift tests.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the Lachman test has been the most accurate and reliable for diagnosing an ACL rupture, 22 and the pivot-shift test is notably thought of as the least sensitive of the three. 8 , 9 , 14 , 17 , 23 Previous studies 7 , 19 have demonstrated the lever sign test to be more sensitive in correctly diagnosing both acute and chronic ACL tears, as well as complete and partial ACL tears, as compared with the anterior drawer, Lachman, and pivot-shift tests.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI-compatible devices of previous studies applied neither an axial compression load, reproducing gravity without additional stress, 10 , 48 , 50 nor a sagittal force on the knee. 14 , 34 Logan et al 33 and Al-Dadah et al 2 assessed the tibiofemoral relationship using weightbearing MRI. They found that the most pronounced effect of the ACL deficiency was the anterior displacement of the lateral tibial plateau relative to the lateral femoral condyle compared with that of the medial side.…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the motion during Lachman test in a real clinical setting, in vivo studies without anesthesia are necessary. Logan et al 14) evaluated the Lachman test results of awake participants. The study evaluated the three static points; reverse Lachman, neutral and Lachman, using open MRI.…”
Section: Discussionmentioning
confidence: 99%
“…However, because soft tissue markers have a mismatch between the skin and the bone and bony markers can only be used under anesthesia, these studies only assessed the knee joint under sedation or the cadaveric knees. Two studies performed 3D analysis during Lachman test without anesthesia 14 15) , but they evaluated only static points: neutral, reverse Lachman and Lachman test using open magnetic resonance imaging (MRI) 14) ; neutral and Lachman test using computed tomography (CT) scan 15) .…”
Section: Introductionmentioning
confidence: 99%